(untitled) (Journal of the College of Basic Education, 2022)
The research included five chapters. The first chapter contained the introduction of the research and its importance. Ethics and their important role in the lives of peoples of different races, places of existence, religions and philosophies they adopted were addressed. The impact of morals is reflected in the behavior of individuals. Education from the point of view of school principals. The aim of the research is to identify the ethics of educational work. The research community is represented by a group of Baghdad education directors / Karkh 1,2,3 and a group of directors of Rusafa Education 1,2,3, whose number is (387) principals. The two researchers built a scale to extract the results, and the researchers concluded The teachers of physical education in middle schools working in Baghdad have an average level of educational work ethics.